INTEGRASI KEARIFAN LOKAL DALAM PERENCANAAN DESTINASI WISATA BUDAYA: KAMPUNG TEMATIK ADAT RIMBO TAROK PADANG - Triska Marvidola; Yosi Suryani; Riani Sukma Wijaya; Vidya Chandra Prashanty; Fauziah Fitri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to analyse the integration of local wisdom into cultural tourism destination planning in the Rimbo Tarok Traditional Thematic Village, Padang City. A descriptive quantitative approach was employed, focusing on five destination planning dimensions: attraction, accessibility, amenities, ancillary services, and promotion. Primary data were collected through questionnaires distributed to 55 respondents, consisting of 50 statement items measured using a five-point Likert scale. Data were analyzed using IBM SPSS Statistics through validity testing, reliability testing, descriptive statistics, and a One-Sample t-Test with a test value of 3. The results showed that all questionnaire items were valid and the overall instrument demonstrated excellent reliability, with a Cronbach’s Alpha of 0.963. Attraction obtained the highest mean score (3.738), followed by amenities (3.480), accessibility (3.251), promotion (3.138), and ancillary services (2.951). Overall, the mean score was 3.312, with t = 3.954 and p < 0.001. These findings indicate that local wisdom-based destination planning is generally perceived positively. However, strengthening ancillary services, institutional management, and tourism promotion should be prioritized to support the sustainable development of Rimbo Tarok as a cultural tourism destination. Keywords: Local Wisdom; Destination Planning; Cultural Tourism; Thematic Village; Sustainable Tourism.   Abstrak: Penelitian ini bertujuan menganalisis integrasi kearifan lokal dalam perencanaan destinasi wisata budaya di Kampung Tematik Adat Rimbo Tarok, Kota Padang. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan lima dimensi, yaitu atraksi, aksesibilitas, amenitas, ancillary service, dan promosi. Data diperoleh melalui kuesioner kepada 55 responden yang dipilih menggunakan Teknik purposive sampling meliputi akademisi, pemerintah, masyarakat, pokdarwis dan pengunjung. Dengan 50 butir pernyataan menggunakan skala Likert 1–5. Analisis dilakukan menggunakan IBM SPSS Statistics melalui uji validitas, reliabilitas, statistik deskriptif, dan One Sample t-Test dengan nilai pembanding 3. Hasil penelitian menunjukkan seluruh item valid dan instrumen memiliki reliabilitas sangat baik dengan Cronbach’s Alpha sebesar 0,963. Nilai rata-rata tertinggi terdapat pada atraksi (3,738), diikuti amenitas (3,480), aksesibilitas (3,251), promosi (3,138), dan ancillary service (2,951). Secara keseluruhan, nilai rata-rata sebesar 3,312 dengan t = 3,954 dan p < 0,001. Hasil ini menunjukkan bahwa perencanaan destinasi berbasis kearifan lokal dinilai positif, namun penguatan layanan pendukung, kelembagaan, dan promosi masih perlu diprioritaskan. Kata kunci: Kearifan Lokal; Perencanaan Destinasi; Wisata Budaya; Kampung Tematik; Wisata Berkelanjutan.